A common variant in the FTO locus is associated with waist-hip ratio in Indian adolescents - Vasan, S; Fall, T; Job, V; Gu, H; Ingelsson, E; Brismar, K; Karpe, F; Thomas, N (2013)
Background: Common variants in the FTO locus, and near MC4R locus, have been shown to have a robust association with obesity in children and adults among various ethnic groups. Associations with obesity traits among Indian adolescents have not been determined. Objective: To study the association of rs9939609 (FTO) and rs17782313 (MC4R) to obesity related anthropometric traits in Indian adolescents. Methods: Subjects for the current study were recruited from a cross-sectional cohort of 1,230 adolescents (age mean ± SD: 17.1 ± 1.9 years) from South India. Results: The variant at the FTO locus was found to be associated with waist-hip ratio (WHR) but not with overall obesity in this population. No significant association was observed for obesity-traits and Mc4R variant rs17782313. Conclusion: The common variant of FTO (rs9939609) is associated with body fat distribution during early growth in Indian adolescents and may predispose to obesity and metabolic consequences in adulthood. © 2012 The Authors.